EVALUASI TINDAK LANJUT PENGELAKAN PAJAK MODUS CROSS-BORDER TRANSACTION DI INDONESIA DENGAN KEBIJAKAN AUTOMATIC EXCHANGE OF INFORMATION FOR TAX PURPOSE - Mohammad, Ryan; Rizal, Helmi Zus (Scientax, 2019)
The Implementation of Exchange of Information for Tax Purposes policy in the second quarter of 2017 is Indonesian Government efforts to mitigate tax avoidance behavior by using a cross-border transaction. In this paper, we research the effect of the policy to Indonesian resident behavior compliance with Difference-in-difference research design using cross-border deposit Indonesian resident data as a proxy for behavior compliance Indonesian resident who does cross border transaction. The observation started from the first quarter of 2008 until the first quarter of 2019, which results in the decrease of cross-border deposit Indonesian resident in Offshore Financial Centre about 25,9%. Furthermore, the results continue that not every cross-border deposit Indonesian resident repatriated or declared in Indonesian, but shifting into other countries who had not to comply to exchange of information policies around 4,6%. These results suggest that the implementation exchange of information for tax purpose policies had a significant role to increase the enforce compliance behavior of Indonesian resident.